Numerical simulation of the ignition of liquid fuel with a limited-energy source under turbulent flow conditions; Russian Journal of Physical Chemistry B; Vol. 7, iss. 3 - Kuznetsov G. V. Geny Vladimirovich (2013, 2013)
Title screen